Penggunaan Media Pembelajaran Bahasa Arab Berbasis Audio Visual - Nur Khoirotus Syifa; Wulan Indah Fatimaul Djamilah (LP2M IAI Darussalam Martapura, 2024)
Abstract The use of audio-visual based Arabic language learning media is increasingly important in increasing learning effectiveness. This research aims to analyze the impact of audio-visual media on students' Arabic language skills. By utilizing videos, audio recordings and interactive presentations, learning becomes more interesting and interactive. The research method used is a case study in several secondary schools that implement this media in their curriculum. By using relevant technology, students can more easily understand the cultural and linguistic context of Arabic. Overall, the integration of audio-visual media in Arabic language learning has the potential to increase the effectiveness and efficiency of the teaching and learning process. The results show that students who learn with audio-visual media show significant improvements in listening, speaking and vocabulary comprehension skills. Apart from that, this media also contributes to increasing students' motivation and interest in Arabic. This research recommends wider integration of audio-visual media in Arabic language learning to achieve better results. Keywords: Learning media, Arabic, Audio-Visual Abstrak Penggunaan media pembelajaran bahasa Arab berbasis audio visual semakin penting dalam meningkatkan efektivitas pembelajaran. Penelitian ini bertujuan untuk menganalisis dampak media audio visual terhadap kemampuan berbahasa Arab siswa. Dengan memanfaatkan video, rekaman audio, dan presentasi interaktif, pembelajaran menjadi lebih menarik dan interaktif.[1] Metode penelitian yang digunakan adalah studi kasus di beberapa sekolah menengah yang menerapkan media ini dalam kurikulum mereka. Dengan menggunakan teknologi yang relevan, siswa dapat lebih mudah memahami konteks budaya dan linguistik bahasa Arab. Secara keseluruhan, integrasi media audio visual dalam pembelajaran bahasa Arab berpotensi untuk meningkatkan efektivitas dan efisiensi proses belajar mengajar. Hasil menunjukkan bahwa siswa yang belajar dengan media audio visual menunjukkan peningkatan signifikan dalam keterampilan mendengarkan, berbicara, serta pemahaman kosakata. Selain itu, media ini juga berkontribusi dalam meningkatkan motivasi dan minat siswa terhadap bahasa Arab. Penelitian ini merekomendasikan integrasi media audio visual secara lebih luas dalam pembelajaran bahasa Arab untuk mencapai hasil yang lebih baik Kata Kunci: Media pembelajaran, Bahasa Arab, Audio-Visual